Influence of Stearic Acid and Triethanolamine on the Physical Properties and Antibacterial Efficacy of Ocimum basilicum L. Anti-acne Cream against Staphylococcus epidermidis - Nurcahya, Salsabila; Pranata, Yovi; Pratamarta, Meliasi Nora; Hidayati, Nurul; Setiawansyah, Arif (Journal of Food and Pharmaceutical Sciences, 2025)
Acne vulgaris represents a significant dermatological concern, with Staphylococcus epidermidis identified as a key pathogenic contributor. While Ocimum basilicum L. (basil) leaves contain bioactive compounds including flavonoids, eugenol, and tannins that demonstrate promising antibacterial properties, the successful translation of these natural antimicrobials into effective topical formulations remains critically dependent on appropriate excipient selection. Despite the growing interest in botanical-based acne treatments, there exists a significant knowledge gap regarding how emulsifying agents, particularly stearic acid and triethanolamine (TEA), influence both the physical stability and therapeutic efficacy of herbal cream formulations. This study investigated the effects of varying concentrations of stearic acid and TEA on the physical characteristics, stability, and antibacterial activity of basil leaf extract cream formulations against S. epidermidis ATCC-12228. Extracts obtained via maceration in 96% ethanol were incorporated into cream formulations (F0–F4), which were subsequently evaluated for organoleptic properties, homogeneity, spreadability, adhesion, pH, stability using a thermal cycling test, and antibacterial activity via disc diffusion. Stability assessment revealed notable differences across formulations. Although all formulations maintained consistent pH values and exhibited uniform microscopic homogeneity after cycling, variations in spreadability and adhesion indicated differing degrees of structural stability. Formulations F3 and F4 showed minimal changes across cycles, demonstrating superior resistance to thermal stress, whereas F0 exhibited significant instability in both spreadability and adhesion. Antibacterial testing showed that the formulation containing 20% basil extract (F4) produced the largest inhibition zone (11.83 ± 0.77 mm). Beyond its higher extract content, F4’s superior antibacterial performance is attributed to its more stable structural matrix, which likely enhanced the release and bioavailability of active phytochemicals such as eugenol and flavonoids, thereby promoting more efficient diffusion into the agar medium. Overall, the findings demonstrate that stearic acid and TEA concentrations substantially influence both the physical stability and antibacterial efficacy of basil-based cream formulations. The optimal stability and enhanced antimicrobial activity observed in F3 underscore their potential as promising candidates for topical anti-acne product development.